Pengaruh Daun Jambu Biji dan Tepung Beras sebagai Masker untuk Perawatan Kulit Wajah Berjerawat - Tiara Laila Putri; Mitra Lusiana (STIKes Ibnu Sina Ajibarang, 2025)
This research addresses skin abnormalities in acne-prone individuals by exploring the effectiveness of natural face masks as preventive care. Specifically, it analyzes the impact of a face mask made from guava leaves and rice flour, applied once every seven days over a two-month period. The study adopts a quasi-experimental approach using a Nonequivalent Control Group Design, with participants selected from the 2020 cohort of Universitas Negeri Padang through purposive sampling. Data were collected via observation, documentation, and assessment sheets, and analyzed using Normality, Homogeneity, and Hypothesis Tests. The Normality Test results indicate that the data is normally distributed, as the significance (Sig.) values for all indicators—color (0.200), shape (0.082), volume (0.109), and amount (0.082)—are above the alpha value of 0.05. Similarly, the Homogeneity Test shows significance values greater than 0.05 for all indicators, confirming that the data is homogeneous. The Hypothesis Test, conducted using a T-test, reveals significant differences between the control and treatment groups, with p-values below 0.05 for all indicators: color (<0.001), shape (0.002), volume (0.003), and amount (0.008). These findings lead to the acceptance of the alternative hypothesis (Ha), indicating a significant effect of the guava leaf and rice flour face mask treatment on acne-prone skin. In conclusion, the study confirms that the treatment group (X2) experienced significant improvements compared to the control group (X1).